Influence of Kinetics Concrete Hardening on Strength of Constructions - Berlinov Mikhail; Berlinova Marina (MATEC Web of Conferences, 2016)
In this article the question of the influence of the kinetics of hardening concrete on its strength in building structures through the stress function. Determined a direct correlation between the optimal structure of concrete and a guarantee of high strength and durability of building structures that ensured a coincidence given the amounts and extreme properties. A method for predicting the elastic properties of concrete based on known theory of strength of concrete model. It is shown by way of example, that in certain specific strength characteristics of concrete, properties of its components (cement stone and aggregates), the maximum value of the short-term strain, creep deformation and modulus of elasticity of concrete depends on its strength at the time of loading. The proposed method is the most convenient for practical approximation to obtain the equations of mechanical state to determine the total deformation of concrete.In this article the approach to determine the strength of concrete in building structures through the stress function under load. It is shown by way of example, that the results obtained by experiment and the proposed article approach to the assessment of the strength to coincide with high accuracy.